Methanogens Within a High Salinity Oil Reservoir From the Gulf of Mexico - Christman, Glenn D.; León-Zayas, Rosa I.; Summers, Zarath M.; Biddle, Jennifer F. (Frontiers in Microbiology, 2020)
Oil reservoirs contain microbial populations that are both autochthonously and allocthonously introduced by industrial development. These microbial populations are greatly influenced by external factors including, but not limited to, salinity and temperature. In this study, we used metagenomics to examine the microbial populations within five wells of the same hydrocarbon reservoir system in the Gulf of Mexico. These elevated salinity (149-181 ppt salinity, 4-5X salinity of seawater) reservoirs have limited taxonomic and functional microbial diversity dominated by methanogens, Halanaerobium and other Firmicutes lineages, and contained less abundant lineages such as Deltaproteobacteria. Metagenome assembled genomes (MAGs) were generated and analyzed from the various wells. Methanogen MAGs were closely related to Methanohalophilus euhalobius, a known methylotrophic methanogen from a high salinity oil environment. Based on metabolic reconstruction of genomes, the Halanaerobium perform glycine betaine fermentation, potentially produced by the methanogens. Industrial introduction of methanol to prevent methane hydrate formation to this environment is likely to be consumed by these methanogens. As such, this subsurface oil population may represent influences from industrial processes.